(untitled) (World Journal of Current Medical and Pharmaceutical Research, 2020)
Alstorm Syndrome , a recessively inherited autosomal rare genetic disorder usually caused by the mutations in ALSM 1 gene located on chromosome 2p13 characterised by the progressively developing multi organ pathology from the infancy stage but the exact function of ALSM 1 gene was still unknown. Alstorm Syndrome encompasses Cone Rod Retinal Dystrophy, Loss of Hearing, Truncal Obesity, Hypertriglyceridemia, Hyperinsulinemia, Insulin Resistance, Dilated Cardiomyopathy, Progressive Hepatic, Renal and Pulmonary Dysfunction Short Stature Infertility and normal intelligence but delayed psychomotor and intellectual development. Acquiring Clinical features, Age of Onset and severity of disease vary greatly among and even within family bearing identical mutations due to interactions of genetic modifiers. Progressive development of multiorgan damage leads to reduced lifespan not exceeding 50 years. Diagnosis is usually based on the clinical features observed but due to delay of onset of symptoms molecular genetic tests at any age confirms the diagnosis of disease. Due to gradual evolvement and variability of expression leads to delay in onset of symptoms which often leads to misdiagnosis. So far, there is no specific treatment that can cure, prevent or reverse the medical complications associated with Alstorm Syndrome. Early assessment of the disease, intensive medical management and multidisciplinary approach can detect and anticipate the complications that can be prevented and treated. Close monitoring, Prompt inter